2021
DOI: 10.5195/emaj.2021.237
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management and Competitive Advantage of Listed Consumer Goods Manufacturing Companies in Nigeria

Abstract: The study investigated the effect of knowledge management on the competitive advantage of Nigerian consumer goods businesses. A survey research design was used for the study. The management staff of six major consumer goods firms were included in the study’s population: Flour Mills Nigeria Plc., Cadbury Nigeria Plc., Guinness Nigeria Plc., Nestle Nigeria Plc., Honeywell Flour Mills and PZ Cussons Nigeria from which a sample of 384 was drawn using power analysis. A structured questionnaire was used to collect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…Therefore, it was established that knowledge sharing had statistical relationship with market share of manufacturing SMEs in South Eastern, Nigeria. This result was in line with previous studies (Akpobome, 2021;Bhawiya Roopaa & Gopinath, 2021;Onifade et al, 2022;Shodiya, 2021;Stephen, 2022).…”
Section: Test Of Hypothesis Onesupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore, it was established that knowledge sharing had statistical relationship with market share of manufacturing SMEs in South Eastern, Nigeria. This result was in line with previous studies (Akpobome, 2021;Bhawiya Roopaa & Gopinath, 2021;Onifade et al, 2022;Shodiya, 2021;Stephen, 2022).…”
Section: Test Of Hypothesis Onesupporting
confidence: 93%
“…Jue, Marr, and Kassotakis (2010) suggested that associations can use knowledge to gain competitive advantage and that successful association's use knowledge to improve their products and services. Stephen (2022); Samir (2020); Shodiya (2021); Bhawiya Roopaa and Gopinath (2021); Okoli, Onochie, Ngige, and Okaforocha (2021); Adhikari (2020); Dickson and Isaiah (2019) and Ireri (2013) found that Knowledge sharing improved the competitiveness of the associations by adding customer satisfaction, participation in requests, reduction of operating costs, business performance and also the resignation and operation of new technologies. Based on the above discussions, the following hypothesis was developed: H1: There is no significant association among knowledge sharing and market share for manufacturing SMEs in South-East, Nigeria.…”
Section: Knowledge Sharing and Market Sharementioning
confidence: 99%
See 2 more Smart Citations
“…Another critical part of the company's KBV is the requirement for knowledge integration in all organizational processes. The ability to integrate and use knowledge has an impact on the relationship between organizational knowledge and a firm's competitive advantage (Shodiya, 2021). Håkanson, (2010), opine that many of the core assumptions of the knowledge-based view have remained debatable.…”
Section: Resource-based Theoriesmentioning
confidence: 99%